Relationship between Lipoprotein Lipase Derived from Subcutaneous Adipose Tissue and Cardio-Ankle Vascular Index in Japanese Patients with Severe Obesity - Atsuhito Saiki; Yuka Takahashi; Shoko Nakamura; Shuhei Yamaoka; Kazuki Abe; Sho Tanaka; Yasuhiro Watanabe; Takashi Yamaguchi; Daiji Nagayama; Masahiro Ohira; Takashi Oshiro; Ichiro Tatsuno; et al. (Obesity Facts, 2024)
Introduction: Cardio-ankle vascular index (CAVI) is an arterial stiffness index that correlates inversely with body mass index (BMI) and subcutaneous fat area. Lipoprotein lipase (LPL) that catalyzes the hydrolysis of serum triglycerides is produced mainly in adipocytes. Serum LPL mass reflects LPL expression in adipose tissue, and its changes correlate inversely with changes in CAVI. We hypothesized that LPL derived from subcutaneous adipose tissue (SAT) suppresses the progression of arteriosclerosis and examined the relationship of LPL gene expression in different adipose tissues and serum LPL mass with CAVI in Japanese patients with severe obesity undergoing laparoscopic sleeve gastrectomy (LSG). Methods: This study was a single-center retrospective database analysis. Fifty Japanese patients who underwent LSG and had 1-year postoperative follow-up data were enrolled (mean age 47.5 years, baseline BMI 46.6 kg/m2, baseline HbA1c 6.7%). SAT and visceral adipose tissue (VAT) samples were obtained during LSG surgery. LPL gene expression was analyzed by real-time PCR. Serum LPL mass was measured by ELISA using a specific monoclonal antibody against LPL. Results: At baseline, LPL mRNA expression in SAT correlated positively with serum LPL mass, but LPL mRNA expression in VAT did not. LPL mRNA expression in SAT was correlated, and serum LPL mass tended to correlate inversely with the number of metabolic syndrome symptoms, but LPL mRNA expression in VAT did not. LPL mRNA expression in SAT and CAVI tended to correlate inversely in the group with visceral-to-subcutaneous fat ratio of 0.4 or higher, which is considered metabolically severe. Serum LPL mass increased 1 year after LSG. Change in serum LPL mass at 1 year after LSG tended to be an independent factor inversely associated with change in CAVI. Conclusions: Serum LPL mass reflected LPL mRNA expression in SAT in Japanese patients with severe obesity, and LPL mRNA expression in SAT was associated with CAVI in patients with visceral obesity. The change in serum LPL mass after LSG tended to independently contribute inversely to the change in CAVI. This study suggests that LPL derived from SAT may suppress the progression of arteriosclerosis.